Odpowiedzi

2009-12-12T15:14:10+01:00
-(3x-2)²+(2x – 3) • ( 2+3x) ≤ 6x(5-0,5x) + x+ 5
-9x² + x + 4 + 4x + 6x² - 6 - 9x ≤ - 9x + 5
-9x² + x+ 4x + 6x²- 9x - 9x ≤5 -4 + 6
2009-12-12T15:19:23+01:00
- [ 3x-2]* [3x-2]+4x+6x-6-9x ≤ 30x-3x²+x+5
-9x²+6-6x+4+x-6 ≤ 31 x- 3x²+5
-9x²+10-5x-6 ≤31x-3x²+5
-9x²-5x-31x+3x² ≤5-10+6
-6x²-36x ≤-1
2009-12-12T15:20:14+01:00
-(3x-2)²+(2x – 3) • ( 2+3x) ≤ 6x(5-0,5x) + x+ 5
-(9x²-12x+4)+4x+6x²-6-9x≤30x-3x²+x+5
-9x²+12x-4+4x+6x²-6-9x-30x+3x²-x-5≤0
-23x-15≤0
-23x≤15
x≥-15/23